Tensile mechanical properties of greenhouse cucumber cane - Yunfeng, Xu; Xiliang, Zhang; Xiaojia, Sun; Jizhang, Wang; Jizhan, Liu; Zhiguo, Li; Qian, Guo; Pingping, Li (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: To obtain the mechanical properties of greenhouse cucumber cane, tensile and shear properties of the greenhouse cucumber cane were studied by using computer-controlled electronic universal testing machine and homemade cutting test bench, respectively. Firstly, the root, middle and head of cucumber cane were subjected for tensile tests. The tensile stress-strain curves showed that the root of cumber cane presented the characteristics of plastic material, while the middle and head showed the characteristics of brittle material. The average tensile strength of root, middle and head of fresh cucumber cane were 7.35 MPa, 6.30 MPa and 4.68 MPa, respectively. The average elastic modulus of root of fresh cucumber cane was 280.58 MPa, which was much greater than the middle and head with average elastic modulus of 198.81 MPa and 137.22 MPa, respectively. A pendulum impact cutting test-rig and a cutting force measurement system composed of a cantilever weigh sensor, a high frequency DAQ card and motion control card were developed. The cutting mechanical property experiments of different parts of greenhouse cucumber cane were carried out, and the continuous curves of cutting force were measured. The single factor test for cross-sectional area, cutting speed, cutting tool type and manner were analyzed. The results indicated that the peak cutting force increased approximately linearly with the increasing of cutting sectional area, but decreased gradually with the increasing of cutting speed. In the same conditions, the cutting force could be reduced by using straight blade cutting tool and ramp cutting way. Through the multifactor interaction impact test of the cutting way, the blade type and the cutting speed, it was found that the corresponding F-value of the three factors were 21.316, 49.141 and 0.222, which suggests that the blade type is the most significant factor for the cutting force.Keywords: cucumber cane, mechanical properties, modulus of elasticity, tensile strength, cutting forceDOI: 10.3965/j.ijabe.20160905.1725Citation: Xu Y F, Zhang X L, Sun X J, Wang J Z, Liu J Z, Li Z G, et al. Tensile mechanical properties of greenhouse cucumber cane. Int J Agric & Biol Eng, 2016; 9(5): 1－8.